Vegetal Cinema in Christine Montalbetti’s Novel Western - Bédard-Goulet, Sara (Literatūra, 2022)
This article examines the vegetal agency taking place in the novel Western (2005) (Western: A Novel, translated by Betsy Wing in 2009) by contemporary French writer Christine Montalbetti. Building on the cinematographic performativity of the novel itself and on a materialist ecocritical approach, it studies the mobility of plants in this narrative to identify how the cinematographic transmediality contributes to engage the vegetal in the foreground. This analysis allows to feed the characterisation of cinematographic devices in the contemporary novel and to prolong the reflection on nonhuman agency and its presence in literature today.